Process management and its incidence in the operational costs of public institutions: National Superintendency of State Property - Palmer Torres, Jussara Inez Anaí (2018)
Objective: To determine the incidence of the Affectation process in the use of the properties in the management of the real estate of the State administered by the National Superintendence of State Property, period 2012 - 2016. Method: It is a substantive, explanatory, quantitative, transversal research and a retrospective, correlational and non-experimental one, based on measurement, numerical evaluation and statistical analysis. Results: The sample consisted of 20 applications, to which the chi-square tests were applied and then the variables were related; the results indicated that the time of the evaluation, execution and registration procedures does affect the management of the State's real estate administered by the NATIONAL SUPERINTENDENCY OF STATE PROPERTY (SBN) . Conclusions: The importance of Process Management as a cornerstone in public affairs is economically and socially profitable, thus contributing to its modernization. The Affectation process in the use of the properties was improved and the process map and value chain of the SBN were designed, due to its positive systemic impact on the management of the State's real estate.